1998
DOI: 10.1096/fasebj.12.13.1397
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage measured in human lymphocytes: large differences between sexes and between countries, and correlations with heart disease mortality rates

Abstract: The 'antioxidant hypothesis' proposes that vitamin C, vitamin E, carotenoids, and other antioxidants occurring in fruit and vegetables afford protection against heart disease and cancer by preventing oxidative damage to lipids and to DNA, respectively. To test elements of this hypothesis, we have measured blood levels of dietary antioxidants, and 8-oxodeoxyguanosine (8-oxo-dG) concentrations in lymphocyte DNA, in healthy men and women from five European countries: France, Ireland, The Netherlands, Spain, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 9 publications
5
72
0
Order By: Relevance
“…Both M1dG and 8-oxodG adducts showed a weak correlation with vitamin A levels, which persisted for M1dG only at the mutivariate analysis, where the data were adjusted for possible confounders; in this analysis, age became the predominant independent determinant of oxidative damage. Similar findings were reported by a study conducted in five European countries (31), and by a study involving men on high fruit and vegetable diets (32). A study involving coke-oven workers who took vitamin supplements showed that the excretion of 8-oxodG adducts was decreased compared to those workers that took no vitamins (33).…”
Section: Discussionsupporting
confidence: 80%
“…Both M1dG and 8-oxodG adducts showed a weak correlation with vitamin A levels, which persisted for M1dG only at the mutivariate analysis, where the data were adjusted for possible confounders; in this analysis, age became the predominant independent determinant of oxidative damage. Similar findings were reported by a study conducted in five European countries (31), and by a study involving men on high fruit and vegetable diets (32). A study involving coke-oven workers who took vitamin supplements showed that the excretion of 8-oxodG adducts was decreased compared to those workers that took no vitamins (33).…”
Section: Discussionsupporting
confidence: 80%
“…General characteristic of the analytical parameters of the study groups is described in the 14 We did not, however, find any difference in 8-oxodGuo level between men and women in the studied groups.…”
Section: Resultsmentioning
confidence: 60%
“…14,15 We examine whether this level in lymphocytes DNA is higher in colon cancer patients when compared to the control group. Factors that may influence oxidative stress such as antioxidant vitamins and uric acid were also determined.…”
mentioning
confidence: 99%
“…Antioxidants present in the diet in theory should provide protection against the deleterious effects of xenobiotics that have the potential or lead to the induction of oxidative stress [31] and [32]. There was no significant correlation found for individuals between the levels of vitamin A, vitamin E, vitamin C and folate with individuals from five European countries [33]. A study involving men on high fruit and vegetable diets again failed to find any correlation with level of 8-oxodG adducts excreted into the urine [34].…”
Section: Discussionmentioning
confidence: 91%